Taking Money Seriously and Putting it Back into the Feldstein-Horioka Saving-Investment Nexus - Kam Hon Chu (Credit and Capital Markets – Kredit und Kapital, 2022)
Theoretically based on national income accounting identities, the Feldstein-Horioka hypothesis downplays, if not totally ignores, the influence of monetary factors on international capital mobility. Recognizing the historical development of economics and the institutional arrangements of the exchange rate regime, this study extends the theoretical framework by integrating the balance of payments and national income accounting equations to show that domestic investment is related to not only domestic saving and international capital flows but also changes in the domestic money supply and credit creation. Panel data regression results for the original Feldstein-Horioka sample~– 20 OECD countries over the years 1960?–?1974~– empirically support the theory. In contrast to the Feldstein-Horioka findings, a lower saving-investment coefficient is found, suggesting higher international capital mobility though still with some degree of home bias. Overall, this study illustrates the importance of money, history of economics and economic institutions in understanding and resolving the Feldstein-Horioka puzzle.
Keywords: E2; E5; F3; F4; 330; Feldstein-Horioka Puzzle; International Capital Mobility; Investment-Saving Correlation; Monetary Approach to the Balance of Payments; Panel Data Econometrics